2023
DOI: 10.1101/2023.02.14.23285933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants associated with infant mortality in Ethiopia: Using the recent 2019 Ethiopia mini demographic and health survey

Abstract: Background Infant mortality is the number of deaths under the age of one year and it is one of the most essential and sensitive indicators of the health status of the country. This study aims to identify the determinants that affect infant deaths in Ethiopia using the 2019 EMDHS. Methods This study used the 2019 Ethiopia mini demographic and health survey and 1,397 infants born from mothers who had been interviewed about births in the five years before the survey. The data were first analyzed with a chi-square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…They found that STs had the highest child mortality rates, in uenced by factors such as residence, maternal education, socioeconomic status, and family size. [22] Examined factors contributing to high infant and child mortality in 14 African countries from 2000 to 2018, identifying public health spending, number of physicians, globalization, economic growth, education, governance, and HIV incidence as signi cant determinants. [20] used logistic regression to analyze 41,668 Nigerian households and revealed the highest infant mortality rates in the Northwest and Northeast Regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that STs had the highest child mortality rates, in uenced by factors such as residence, maternal education, socioeconomic status, and family size. [22] Examined factors contributing to high infant and child mortality in 14 African countries from 2000 to 2018, identifying public health spending, number of physicians, globalization, economic growth, education, governance, and HIV incidence as signi cant determinants. [20] used logistic regression to analyze 41,668 Nigerian households and revealed the highest infant mortality rates in the Northwest and Northeast Regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, in 2019, SSA countries were the leading global region by U5CM, with 75.8 deaths per 1,000 live births and significant disparities between urban and rural areas (44.27% vs. 74.7%) [7,[18][19]. Moreover, under-five children of rural residents are more likely to die before five years [20], and the hazard ratio of being from rural areas varies in Africa, ranging from 1.01 in Zimbabwe to 1.29 in the Democratic Republic of the Congo [19].…”
Section: Introductionmentioning
confidence: 99%